A MULTIDISCIPLINARY APPROACH: LEVERAGING BIOMEDICAL ENGINEERING AND TECHNICIAN EXPERTISE FOR ADVANCED HEALTHCARE SOLUTIONS - Mohammed Ali Alqahtani, Naif Salem Almutairi, Talal Khaled Alkhamali, Sultan Odhab Althafiri, Mohammed Harb Alothman (Chelonian Research Foundation, 2023)
This article explores the symbiotic relationship between biomedical engineering and technical expertise in dental, radiology, and operations technology, emphasizing their collective impact on advancing healthcare solutions. Biomedical engineering, with its foundation in integrating engineering principles with biological sciences, has led to significant innovations in medical devices and procedures. However, the practical application and optimization of these advancements in clinical settings are largely contingent upon the specialized skills of technicians. Through an interdisciplinary lens, this piece delves into the ways in which dental and radiology technicians, alongside operations specialists, play pivotal roles in translating engineering designs into effective healthcare outcomes. It highlights case studies where collaboration between engineers and technicians has led to breakthroughs in patient care, underscoring the importance of a multidisciplinary approach. The article also addresses the challenges inherent in such collaborations, including the need for continuous education and the management of diverse professional languages and perspectives. Looking forward, it speculates on emerging trends and the evolving roles of professionals within this integrated framework, advocating for policies and practices that promote synergy across disciplines to enhance patient care. Keywords: Biomedical Engineering, Dental Technician, Radiology Technician, Operations Technician, Multidisciplinary Healthcare, Medical Devices, Patient Care Innovation, Interdisciplinary Collaboration, Clinical Application, Healthcare Technology